2013
DOI: 10.5007/1980-0037.2013v15n3p305
|View full text |Cite
|
Sign up to set email alerts
|

Controle postural e equilíbrio funcional em indivíduos com neuropatia diabética periférica

Abstract: Grupo de Estudos Mecanismos periféricos da regulação cardiovascular induzidos pelo treinamento físico em diferentes situações.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
1
0
1
Order By: Relevance
“…In addition, in condition 2 with the restriction of higher joints, the mean changes in the APSI and MLSI were about 25% and 9%, respectively. These findings are in line with those obtained by Fortaleza who reported that in diabetic neuropathic patients with sensory impairment of ankle, AP sway was more affected by visual input than ML (44). As a result, the restriction of visual and vestibular systems, as well as the movement of the upper segments, caused more significant changes in AP direction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, in condition 2 with the restriction of higher joints, the mean changes in the APSI and MLSI were about 25% and 9%, respectively. These findings are in line with those obtained by Fortaleza who reported that in diabetic neuropathic patients with sensory impairment of ankle, AP sway was more affected by visual input than ML (44). As a result, the restriction of visual and vestibular systems, as well as the movement of the upper segments, caused more significant changes in AP direction.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, evaluation in different conditions provides a deeper understanding of the relationship between sensory and motor afferents (44).…”
Section: Discussionmentioning
confidence: 99%
“…Eles constataram que houve melhora no deslocamento do plano médio-lateral. Bonfim et al (2007) Nessa abordagem, a intervenção proposta neste estudo concorda com as conclusões de Fortaleza et al (2013) e Iunes et al (2014), os quais ratificaram a necessidade de programas de reabilitação para trabalhar com os componentes sensoriais por meio de exercícios terapêuticos.…”
Section: Discussionunclassified